Pengaruh Kepadatan Calon Induk Ikan Nila (Oreochromis Niloticus) Dengan Menggunakan Anestesi Minyak Cengkeh (Syzygium Aromaticum) Terhadap Tingkah Laku Ikan Pada Simulasi Transportasi - Sitty Andrameda; Suri Purnama Febri; Andika Putriningtias (Jurnal Ilmiah Samudra Akuatika, 2026)
Nile tilapia (Oreochromis niloticus) is one of the most economically important freshwater aquaculture species and is highly susceptible to stress during transportation, making the use of anesthetics essential to improve survival. This study aimed to evaluate the physiological responses and survival of prospective Nile tilapia broodstock at different stocking densities following clove oil (Syzygium aromaticum) anesthesia during simulated transportation. The experiment employed a completely randomized design (CRD) consisting of four stocking density treatments, each with three replicates. The observed parameters included induction time, recovery time, oxygen consumption rate, survival rate, and water quality. The results showed that the longest induction time was recorded in treatment P4 (20 fish), averaging 24.16 minutes, whereas the shortest induction time occurred in treatment P1 (5 fish), averaging 21.48 minutes. Numerically, induction time tended to increase with increasing stocking density. Stocking density significantly influenced the behavioral responses of prospective Nile tilapia broodstock during simulated transportation under clove oil anesthesia. The highest post-transport survival rate was observed in treatment P3 (15 fish), reaching 88.83%, while the lowest survival rate was recorded in treatment P4 (20 fish), at 61.67%.